Creative action in organizations ivory tower visions & real world voices - Ford, Cameron M.; Gioia, Dennis A., 1947-; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1995)
With engaging contributions from leading academics and professionals, this book explores the key factors that are critical to the development and promotion of creativity in any organization.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Creative ability in business; Organizational change; Organizational effectiveness; Industrial management -- Employee participation; Electronic books